Mice With Partial Deletion of Y-Heterochromatin Exhibits Stress Vulnerability - Dey, Sandeep Kumar; Kamle, Avijeet; Dereddi, Ram Reddy; Thomas, Shiju M.; Thummala, Shashi Rekha; Kumar, Arvind; Chakravarty, Sumana; Jesudasan, Rachel A. (Frontiers in Behavioral Neuroscience, 2018)
The role of Y chromosome in sex determination and male fertility is well established. It is also known that infertile men are prone to psychological disturbances. Earlier studies in the laboratory identified genes expressed in testes that are putatively regulated by Y chromosome in man and mouse. With the availability of a Y-deleted mouse model, that is subfertile, we studied the effect of a partial deletion of Y-chromosomal heterochromatin on mouse behaviour when compared to its wild type. The partial Y-deleted mice exhibited anxiety like phenotype under stress when different anxiety (open field test and elevated plus maze test) and a depression related tail suspension test and forced swim test, were performed. The mutant mice also showed significant reduction in hippocampal neurogenesis and altered expression of neurogenesis markers such as Nestin, Sox2, Gfap, NeuroD1 and Dcx using qPCR analysis. The genes with altered expression contained short stretches of homology to Y-derived transcripts only in their Untranslated Regions (UTRs). Our study suggests putative regulation of these genes by the Y chromosome in mouse brain altering stress related behaviour.